Juridical Analysis of the Constitutional Court Decision No. 29/PUU-XIV/2016 About the Attorney General's Authority to Allow Deponering in Indonesia - Wulandari , Ni Kadek Jeany; Sadnyini, Ida Ayu (Hukum Keluarga Islam IAIN LANGSA, 2024)
The authority of the Attorney General to provide assistance in criminal cases or to exercise deponering is a form of discretionary power regulated under Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia. This authority underwent a significant procedural shift following the Constitutional Court Decision Number 29/PUU-XIV/2016. The decision addressed issues with Article 35(c), particularly the phrase requiring the Attorney General to consider the advice and opinions of state power bodies when evaluating the public interest. This study employs normative legal methods with conceptual, statute, case, and comparative approaches. Both primary and secondary legal texts are used. One important thing that makes this study stand out is that it looks closely at the Constitutional Court's decision. This decision is a turning point for making the deferring power process more fair and clear. Unlike other studies, this one focuses on how the decision combines the Attorney General's freedom of choice with ways to stop abuse by making the government more accountable and open. The findings reveal that the Constitutional Court's decision establishes that the advice of state power bodies is not binding but must still be objectively considered by the Attorney General. The decision underscores the importance of transparency in exercising deponering authority, emphasizing the need to base decisions on the public interest. As a result of this ruling, the mechanism for implementing deponering has become more structured and transparent, reducing the risk of abuse of authority by the Attorney General. This study concludes that the Constitutional Court's decision has positively influenced the regulation of criminal law regarding deponering authority in Indonesia and sets a new precedent for the discretionary powers of law enforcement officials.